Technical parameters dynamics of WOODY 110 cable skidder within the range of stopping due to overload in uphill wood skidding - Marenče, Jurij (Zbornik gozdarstva in lesarstva, 2008)
The article deals with uphill wood skidding with WOODY 110 skidder and the changes taking place in technical parameters: slip, torque, tractive forces, and weight distribution of a loaded tractor in the last three meters of skidding, which is defined as a range of stopping due to overload. The test was performed on a concave skid trail, where tractor loaded with 8 meter long fir logs stopped at the 32% incline. It stopped somewhat later when skidding with butt-end forward in comparison to skidding with top-end forward. The loadweight with butt-end forward was 31.69 kN, whereas with top-end forward itweighed 33.53 kN. The measured speeds showed minute changes until the last meter, but decreased swiftly after stopping. Regarding some technical parameters, there were almost no changes at the end of stopping, two exceptions being the slip, which increased in the range of stopping, and the forward torque, which decreased in this range. The results showed that the hydrostatic transmission was efficient, considering that in a relatively well-controlled slip (the slip values increase only in the last three meters, which approximately equals the half of tractor's length) there was less grounddamage.
Keywords: hitrost; Navar; navor; spravilo lesa; traktorji